Kimia Medisinal dan Masa Depan Pengobatan - Desinta Nurohman Husen; Saeful Amin; Karina Budi Arti; Maesaroh Maesaroh (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
This study aims to review the latest developments in medicinal chemistry and its prospects in the development of future treatments. Through a comprehensive literature study approach, this study analyzes the latest innovations in drug design and development, including the use of computational technology, nanotechnology, and biological target-based approaches. The results show that the integration of artificial intelligence and machine learning technologies with conventional medicinal chemistry techniques has opened a new paradigm in more efficient and precise drug discovery. Personalization of treatment based on patient genetic profiles, development of new antibiotics to overcome antimicrobial resistance, and nanomaterial-based therapies are important trends in contemporary medicinal chemistry applications. This study concludes that the future of medicine will be greatly influenced by advances in medicinal chemistry, with the main challenges being safety, regulation, and accessibility.More intensive multidisciplinary collaboration is needed between chemists, biologists, pharmacologists, clinical medicine, and informatics to optimize the potential of medicinal chemistry in the future medicine revolution.